Cationic Carbosilane Dendritic Systems as Promising Anti‐Amyloid Agents in Type 2 Diabetes. Issue 34 (25th May 2020) - Lozano‐Cruz, Tania; Alcarraz‐Vizán, Gema; de la Mata, F. Javier; de Pablo, Sara; Ortega, Paula; Duarte, Yorley; Bravo‐Moraga, Felipe; González‐Nilo, Fernando D.; Novials, Anna; Gómez, Rafael
Abstract: The most common denominator of many of the neurodegenerative diseases is badly folded protein accumulation, which results in the formation of insoluble protein deposits located in different parts of the organism, causing cell death and tissue degeneration. Dendritic systems have turned out to be a promising new therapeutic approach for the treatment of these diseases due to their ability to modulate the folding of these proteins. With this perspective, and focused on type 2 diabetes (T2D), characterized by the presence of deposits containing the amyloidogenic islet amyloid polypeptide (IAPP), we demonstrate how different topologies of cationic carbosilane dendrimers inhibit the formation of insoluble protein deposits in pancreatic islets isolated from transgenic Tg‐hIAPP mice. Also, the results obtained by the modification of dendritic carbosilane wedges with the chemical chaperone 4‐phenylbutyric acid (4‐PBA) at the focal point confirmed their potential as anti‐amyloid agents with a concentration efficiency in their therapeutic action five orders of magnitude lower than that observed for free 4‐PBA. Computational studies, which determined the main interaction between IAPP and dendrimers at the atomic level, support the experimental work. Abstract : Cutting wedge therapy ! We demonstrate how the topology of carbosilane cationic dendrimers linked to the chemical chaperone 4‐phenylbutyric acid influences their therapeutic action as anti‐amyloid agents for type 2 diabetes. Dendritic wedges gave the best results, with low doses of the dendrimers preventing or inhibiting the formation of islet amyloid polypeptide deposits in pancreatic islets isolated from Tg‐hIAPP mice (see figure).